The Use of Off-label and Unlicensed Drugs for Neonates: A Report from a Teaching Hospital in Baghdad - Hameed, Numan N.; Abbas , Shealan Kh. (Journal of the Faculty of Medicine Baghdad, 2023)
Background: Neonates who are admitted to hospitals will need various drugs. The use of unlicensed or off-label drugs without scientific evidence makes this exposure unsafe. Aim of study: We aimed to assess the use of drugs for neonates based on the British National Formulary for Children and IBM Micromedex Neofax. Patients and methods: This is a descriptive study which reviewed the clinical files of enrolled neonates who have stayed in the hospital for more than 24 hours and received at least one drug. It was conducted in the neonatal care unit of the Children Welfare Teaching Hospital/ Medical City Complex in Baghdad during the period from 1st of January to 30th of June/2018. The data was entered on a predesigned format and analyzed by using the appropriate statistical methods. Results: A total number of 1079 neonates were admitted to the NCU during the study period, of whom 967 were included in the current study with 597 (61.7%) males and 370 (38.3%) females. There were 424 (43.8%) preterm, 496 (51.3%) term and post term neonates, and 47 (4.9%) neonates with unknown gestational age. Different classes of drugs were used with a total of 56 drugs, of which 33.9% were unlicensed and 66.1% were off-label. Accordingly, 42.5% of the neonates received unlicensed drugs and almost all patients received at least one off-label drug. Major risk factors for such use include mechanical ventilation, male sex and prolonged hospitalization. Conclusions: In hospitalized neonates, drugs were more frequently prescribed as an off-label rather than unlicensed. Almost all neonates were exposed to off-label formulations.